1994
DOI: 10.3171/jns.1994.81.1.0130
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic chordoma

Abstract: The case is reported of a 51-year-old woman found to have a hypothalamic mass with the histological features typical of chordoma. This represents the first description of a chordoma arising within the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…It was a pineal chordoma with abdominal metastasis, due to previous ventriculoperitoneal shunt placement. The origin of such intraparenchymal tumours is not clear and it has been suggested that they arise from ecchordosis physaliphora (EP) or directly from notochord remnants that subsist within brain tissue [8,10]. The cases described suggest ectopic notochordal remnants may be located in different areas, even away from the neuroaxis.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It was a pineal chordoma with abdominal metastasis, due to previous ventriculoperitoneal shunt placement. The origin of such intraparenchymal tumours is not clear and it has been suggested that they arise from ecchordosis physaliphora (EP) or directly from notochord remnants that subsist within brain tissue [8,10]. The cases described suggest ectopic notochordal remnants may be located in different areas, even away from the neuroaxis.…”
Section: Discussionmentioning
confidence: 81%
“…The majority of these lesions were located in the prepontine space. Intradural extraosseous chordomas have occasionally been found within the brain, in hypothalamic and pineal regions [8,10]. Intradural chordomas are believed to be less aggressive and have a better prognosis for patients.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Ecchordosis physaliphora is a small, well-circumscribed intradural lesion usually found on the ventral surface of the brainstem, attached to the dorsum sellae and mostly discovered incidentally at autopsy. [7] Ecchordosis is thought to originate from migration of hamartomatous notochordal remnants to the intradural space via a small opening in the dura.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Ecchordosis is thought to originate from migration of hamartomatous notochordal remnants to the intradural space via a small opening in the dura. [7] Despite the fact that it presents the same histological characteristics of chordoma, it is not a neoplasm[2] and its clinical behavior differs substantially from that of typical chordomas,[7] even though the possibility that intradural extraosseous chordomas may simply be giant ecchordosis physaliphora has also been pointed out. [2]…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Interestingly, multiple reports concern unusual presentations in youngsters, such as: extra clival cranial, intra cerebral, mediastinal, gluteal, etc. [17][18][19][20][21][22][23][24][25][26][27][28][29] Symptoms at presentation depend on the tumor site, and are not specific to children. If they are IC, cranial nerve palsies are seen in 60% or so.…”
Section: Review Of Literaturementioning
confidence: 99%